2008
DOI: 10.1597/07-014.1
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Condyle Lesions in Children with Juvenile Idiopathic Arthritis

Abstract: Children with juvenile idiopathic arthritis presented a remarkable prevalence of condylar destruction, which was correlated to the type and duration of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
14
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 23 publications
4
14
3
Order By: Relevance
“…In the present study, clear abnormalities in the cephalometric examination (above Grade 2 according to the Rohlin and Petersson grading system) were observed in 39.9% of the patients. The findings of the present study confirm the findings of other authors [2,29] that relate the inflammatory process in TMJ to bigger changes, which may include a retrognathic mandible and impaired maximal mouth opening; the range of maximal mouth opening was significantly lower in patients who had suffered from JIA for over 5 years (p < 0.02, Fig. 2).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, clear abnormalities in the cephalometric examination (above Grade 2 according to the Rohlin and Petersson grading system) were observed in 39.9% of the patients. The findings of the present study confirm the findings of other authors [2,29] that relate the inflammatory process in TMJ to bigger changes, which may include a retrognathic mandible and impaired maximal mouth opening; the range of maximal mouth opening was significantly lower in patients who had suffered from JIA for over 5 years (p < 0.02, Fig. 2).…”
Section: Discussionsupporting
confidence: 92%
“…These differences may result either from the degree of severity of the symptoms and articular surface damage, or from the different populations examined the use of different methods of assessing the affected area of the joint [2,7,[18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported frequency of TMJ involvement ranges in the literature from 17% to 87%, depending on the population investigated, the subtypes represented, and the radiologic method by which involvement is diagnosed. [5][6][7][8][9][10][11][12][13][14] Only one study reported the incidence of TMJ involvement in all subtypes of JIA. 6 The most important site of growth of the mandible in the vertical and sagittal direction is located on the articular surface of the condylar head.…”
Section: Introductionmentioning
confidence: 99%
“…6 The most important site of growth of the mandible in the vertical and sagittal direction is located on the articular surface of the condylar head. [12][13][14][15] During nor- mal growth of the dentomaxillary complex, the vertical dimension increases more than the sagittal dimension does. Arthritis of the TMJ results in reduced mandibular growth and subsequent alteration in dental occlusion and may even affect total craniofacial growth.…”
Section: Introductionmentioning
confidence: 99%